MIMO communication system capacity in random visible light channel - A.Y. Parshin; Y.N. Parshin (Компьютерная оптика)
Being a promising one, optical information transmission standard expands capabilities of communication systems in the conditions of heavy frequency band load. Optical communication system efficiency in a room can be improved by multi-antenna systems. The aim of this paper is a theoretical study of MIMO Li-Fi communication system capacity. The calculation of ergodic capacity is performed for MIMO optical communication system in terms of various scenarios of light propagation. Receiving and transmitting system is modeled in the form of receivers and transmitters randomly placed in a room with randomly oriented light-emitting and photo diodes. A matrix of channel parameters is modeled using corresponding probability density functions and additive Gaussian noise at receiver inputs. The paper also considers various scenarios of optical signal propagation and their influence on optical channel capacity. The comparison of various methods of power distribution between original modes of MIMO optical communication system as well as their influence on capacity is carried out. Optimal power distribution between MIMO system eigenmodes is determined by maximum capacity criterion.